2010
DOI: 10.1007/s10681-010-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis

Abstract: Fusarium head blight (FHB) is a serious wheat disease all over the world. In this study, the relationships between plant height (PH) and FHB were investigated across the whole wheat genome by QTL meta-analysis from fifty-six experiments. Coincident meta-QTL (MQTL) for PH and FHB were found on chromosomes 2D, 3A, 4B, 4D and 7A. Rht-B1, Rht-D1, Rht8, MQTLs P7 and P26 were consistent with FHB MQTLs. The meta-analysis results confirmed the negative associations of Rht-B1, Rht-D1, and Rht8 with FHB resistance. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 82 publications
4
57
0
1
Order By: Relevance
“…No correlation was found in populations A and B; the absence of the correlation can be attributed to the small effect size for the heading stage QTL in both populations. Conversely, for plant height, significant correlations between FHB index and plant height were found in all populations, ranging from -0.3 to -0.8, as indicated previously for wheat (29). Accordingly, QTL for plant height overlapped with FHB resistance QTL on chromosomes 2B, 6A, and 5R.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…No correlation was found in populations A and B; the absence of the correlation can be attributed to the small effect size for the heading stage QTL in both populations. Conversely, for plant height, significant correlations between FHB index and plant height were found in all populations, ranging from -0.3 to -0.8, as indicated previously for wheat (29). Accordingly, QTL for plant height overlapped with FHB resistance QTL on chromosomes 2B, 6A, and 5R.…”
Section: Discussionsupporting
confidence: 77%
“…Although the first aspect might have physiological causes based on the DELLA protein which represses gibberellic acid (GA) responsive growth (43), the second aspect is due to direct or indirect effects of height differences per se (10). As explanations, very different effects have been considered, from microclimatic differences between tall and short plants in the field (51) over pleiotropic or morphological effects such as effects of peduncle length and compactness of head to increased cell density of the short plants promoting Fusarium spread in the host tissue (29). Obviously, both aspects are important for long-strawed triticale.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that taller genotypes could maintain a cooler canopy in environments with increased temperatures [46]. A correlation between increased plant height and reduced FHB is reported in numerous studies [47][48][49]. In one study, the investigators showed that plants with Rht-B1b and Rht_D1b significantly decreased resistance to initial infection (Type 1) and Rht_B1b increased resistance to spread of the fungus [42].…”
Section: Discussionmentioning
confidence: 96%
“…Among these, plant height and the extent of retained anthers after flowering play a major role (Buerstmayr et al 2012). Many studies report on the relationship between plant height and FHB resistance -in general, the shorter the plants the more severe are FHB epidemics (Mesterhazy 1995;Hilton et al 1999;Buerstmayr et al 2009;Mao et al 2010). The semi-dwarfing alleles Rht-D1b and Rht-B1b are widely deployed in wheat breeding and both alleles show similar effects on reducing plant height but differ in their impact on FHB resistance.…”
Section: Morphological and Phenological Traitsmentioning
confidence: 99%